Correlation Between Thyroid Hormone Concentrations and Ultrasound Thyroid Volume in Preterm Infants Born Before 33 Weeks of Gestation - Mikołajczak, Aleksandra; Kufel, Katarzyna; Bokiniec, Renata (Frontiers in Endocrinology, 2022)
Objective: Thyroid disorders are commonly concomitant with premature birth; however, indications to start therapy remain unclear due to a lack of gestational age (GA)-specific reference ranges. We aimed to evaluate the age-specific thyroid-stimulating hormone (TSH), free thyroxine (FT4) levels and the correlation between TSH and FT4 serum levels and ultrasound thyroid volume in preterm infants. Materials and Methods: This was an observational, prospective, single-center study of 98 preterm infants born before 33 weeks GA. The infants were divided into the 24-28 weeks and 29-32 weeks GA groups. TSH and FT4 serum levels were measured at two time points: at postnatal age (PNA) 2 weeks and at postmenstrual age (PMA) 32 weeks; the results were compared between groups at two consecutive time points. Results: There was a statistically significant between-group difference in FT4 concentration.There was a positive correlation between FT4 and GA at both screening times. FT4 in the 24-28 weeks GA group was significantly lower than in the 29-32 weeks GA group. The mean (standard deviation [SD]) FT4 at PNA 2 weeks was 11.72±2.16 pmol/l for the 24-28 weeks GA group vs. 13.33±1.80 pmol/l for the 29-32 weeks GA group (p<0.001). The mean (SD) FT4 at PMA 32 weeks was 11.96±1.98 pmo/l for the 24-28 weeks GA group vs. 13.33±1.80 pmol/l for the 29-32 weeks GA group (p=0.001). Our results reflect a slow and gradual upward trend of FT4 in the 24-28 weeks GA. It is of interest that the correlation between thyroid volume and FT4 was statistically significant (rho=0.25, p=0.019) for all studied preterm infants. The correlation between thyroid volume and weight was statistically significant for the entire study group (rho=0.37, p<0.001). We did not find statistically significant differences in TSH and FT4 values between consecutive time points at 24-28 weeks GA. The thyroid volume was not significantly different between both groups. The total thyroid volume was 0.26 vs. 0.27 ml for the 24-28 and 29-32 weeks GA groups, respectively. Conclusion: The results of this study indicate that preterm infants require lower FT4 values depending on GA. Ultrasound thyroid imaging may facilitate the evaluation of questionable thyroid disorders.